Influence of chemerin rs17173608 polymorphism on polycystic ovary syndrome susceptibility - Zahra Movahed; Leila Kohan; Sara Fallahi; Omid Tabiee (Elsevier, 2015)
Objective: The purpose of this study was to assess the association between the rs17173608 chemerin polymorphism and polycystic ovary syndrome risk (PCOS). Materials and methods: This case-control study was performed on 150 patients with PCOS and 150 normal women as the control group. Tetra-amplification refractory mutation system-polymerase chain reaction was used to detect the polymorphism. Results: Our finding showed a positive association between the chemerin gene rs17173608 polymorphism and risk of PCOS. In the dominant effect of the G allele (comparison between TG+GG and TT), TG+GG genotypes were associated with the risk of PCOS (odds ratio = 2; 95% confidence interval = 1.3-3.2, p = 0.003). The G allele is thus dominant and increases the risk of PCOS as compared to the T allele (odds ratio = 1.7, 95% confidence interval = 1.1-2.5, p = 0.009). Nonetheless, there was no significant association between chemerin rs17173608 gene polymorphism and PCOS after adjusting genotypes for body mass index and age. Conclusion: These results suggested that there was a significant association between chemerin rs17173608 polymorphism and the PCOS; but this relationship was affected by obesity status.